Auditor Professionalism and Fraud Prevention: Implications for Good Government Governance - Kurnia Sari Dewi; Paiman Raharjo; Sarida Minarni (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The concept of good governance has become a normative framework in Indonesia, although the application of its principles is still a serious concern. A democratic system requires a government that is accountable, transparent, and free from corruption, collusion, and nepotism. This study aims to examine the influence of forensic audits, investigative audits, authentic professionalism and fraud prevention efforts on the realization of good governance in Audit Board of the Republic of Indonesia (Badan Pengawas Keuangan/BPK). This study uses a quantitative approach. This study used 104 auditors as samples who were selected through purposive sampling with the criteria of having relevant experience in forensic audits and investigative audits. Data was collected using questionnaires and measured using the Likert scale and analyzed with path analysis. The results of this study show that forensic audits, investigative audits, and auditor professionalism have a positive and significant effect on the fraud prevention. In addition, fraud prevention has a positive and significant effect on good governance, which shows that fraud prevention plays a role as a mediation variable. The results of this study highlight the need for public institutions to strengthen their audit functions, especially in the field of forensics and investigation, and to ensure that auditors uphold a high level of professionalism. This effort is necessary to create a strong internal control environment that supports transparent and accountable governance.